mcr-Colistin Resistance Genes Mobilized by IncX4, IncHI2, and IncI2 Plasmids in Escherichia coli of Pigs and White Stork in Spain - Migura-Garcia, Lourdes; González-López, Juan J.; Martinez-Urtaza, Jaime; Aguirre Sánchez, J. R.; Moreno-Mingorance, A.; Perez de Rozas, A.; Höfle, Ursula; Ramiro, Y.; Gonzalez-Escalona, Narjol (Frontiers in Microbiology, 2020)
Colistin has become the last-line antimicrobial for the treatment of multidrug resistant (MDR) enterobacterales in human medicine. Several colistin resistance genes have been detected, with mcr-1 distributed worldwide. The aim of this study was to characterize mcr-mediated resistance plasmids from E. coli of animal origin in Spain. From our strain collection, 70 E. coli of pig origin collected between 2005 and 2014 were randomly selected and screened for the presence of mcr-genes. Additionally, 20 E. coli isolated in 2011 from white storks from the same urban household waste landfill associated colony were also included. Whole genome sequencing of mcr-positive isolates was performed on a MiSeq (Illumina). Hybrid whole genome sequencing strategy combining nanopore and Illumina technologies were performed in a selection of isolates to close the genomes and plasmids and identify the presence of resistance genes. Minimal inhibitory concentration (MIC) was used to assess the susceptibility to colistin. Mating experiments were carried out to evaluate transferability of the mcr-genes. A total of 19 mcr-1 and one mcr-4 positive isolates were detected, 15 from pigs distributed during the study period, and five from storks collected in 2011. The MICs for colistin ranged between ≥4 mg/L. High diversity of STs were detected among the mcr-1 positive E. coli isolates, with only ST-10 shared between pigs and white storks. Except for one isolate, all were genotypic and phenotypically MDR, and five of them also harbored cephalosporin resistance genes (blaCTX-M-14, blaSHV-12 and three blaCMY-2). mcr-1 genes were mobilizable by conjugation, associated with IncX4, IncHI2 and IncI2 plasmids. Regions flanking the transposon varied between plasmids suggesting multiple integration events. In our study mcr-1 genes have been circulating in pig farms since 2005 harbored by a variety of E. coli clones. Its persistence may be driven by co-selection since plasmids containing mcr-1 also exhibit resistance to multiple drugs used in veterinary medicine. Furthermore, this is the first report of the presence of mcr-1 gene in isolates from white storks in Spain. This finding highlights the potential importance of wildlife that forage at urban household waste landfills in the transmission and spread of colistin resistance genes.